Dasar Pertimbangan Hukum Hakim Menjatuhkan Sanksi Dalam Perkara Kekerasan Terhadap Barang - Diska Harsandini (Verstek, 2017)
Demonstration is one part of democratic life to express opinions in public with certain demands to those that sued. Demonstration is legal in a democratic constitutional state and it is guaranteed and protected by law. It applies in Indonesia. Based on the Law No. 9 of 1998 Freedom of Expression in Public that freedom expression in public is a human right which is guaranteed under Article 28 of the Constitution of the Republic of Indonesia 1945.     At the end of 2013, there was a demonstration conducted by two students in Majalengka, namely, Yogi Nandang Ruhiyat and Iwan Sulistiawan, both defendants are members of the PMII organization. The demonstrations ended with vandalism of public facilities and property of PMII organizations. The defendant’s reason to take the action is because their disappointments with the policy of the PMII organization.    The conclusion of this study explained that the basic of decision-making by Supreme Court judges has changed the Bandung High Court Decision No. 172 / PID / 2014 / PT.Bdg is in accordance with applicable laws and regulations. Based on the Supreme Court Decision No. 1217 K / Pid / 2014 that providing sanctions of imprisonment is appropriate because it contains elements of good judgments.     Keywords: demonstrations, basic decision-making, Justices considerations, and the elements of good judgments